Stepwise Formation of Photoconductive Nanotubes through a New Top‐Down Method. (20th October 2015) - Ma, Xiaojie; Zhang, Yibin; Zhang, Yifan; Peng, Cheng; Che, Yanke; Zhao, Jincai
Abstract : In contrast to the widely used bottom‐up strategy for preparing various complex nanostructures, the top‐down strategy is rarely applied to generate complex nanostructures. This study reports the use of a unique combination of bottom‐up and top‐down processes for the time‐resolved stepwise fabrication of novel photoconductive nanotubes from elaborately designed asymmetric perylene diimide molecules.